Enhancing the academic performance of Grade 12 progressed learners in English first additional language - Masuku, Sbonelo Qiniso (University of the Free State, 2023)
The objective of the study was to design a transformatory-bricolage strategy that aims to respond to the challenges faced by Grade 12 progressed learners in English First Additional Language (ENGFAL) in Gert Sibande district secondary schools. The strategy arose against the background of numerous challenges with the current progression policy referred to as National Policy Pertaining to the Program and Promotion Requirements (NPPPPR), which informs the promotion and progression of learners. This study was equally aimed at finding the impact of using bricolage through a transformative paradigm as a scheme to enhance the academic performance of progressed learners in teaching and learning ENGFAL in Grade 12. Learner progression corroborates a challenge facing the South African education system. This qualitative Participatory Action Research furthermore aimed to find possible solutions through bricolage for ENGFAL learners to employ as an intermediation tool to help learners who are progressed through to Grade 12. Data collection tactics used in this study were Focus Group Discussions, semi-structured interviews. Furthermore, data were collected from records such as support policies used at selected schools. The study population was eight Grade 12 learners doing ENGFAL and four educators from two Gert Sibande district schools. Participants were sampled through purposive and convenience sampling. Data were analysed by means of thematic analysis by Laws et al. (2003). Findings from this study showed that transformatory-bricolage could assist in enhancing the academic performance of Grade 12 progressed learners in ENGFAL. The findings additionally indicated that transformatory-bricolage is likely to lessen failure rate which eventually decreases the number of learners who need to be progressed short of meeting promotional requirements. The discoveries also revealed some challenges teachers face in teaching progressed learners, such as a lack of basic understanding of the subject in both grammar and literature, especially the elements of literature. One common feeling was the need for much improved foundations in the lower grades, which prepares learners for the tougher content in the FET phase. Further, findings from this study suggested the need for specialised training and support for teachers in order to assist progressed learners.
Dissertation (M.Ed.(Curriculum Studies))--University of the Free State, 2023
Keywords: English first additional language; Progression policy; Promotion; Participatory action research; Transformative paradigm; Bricolage; Bricoleur; Teacher capacitation; Thematic analysis; Transformatory-bricolage